BIODIVERSITY OF INSECT PESTS OF BT AND NON BT COTTON FIELDS IN NALGONDA DISTRICT, TELANGANA STATE, INDIA - MALLESH, MODALA; SAMMAIAH, CH.; SRAVANTHY, CH. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2021)
Biodiversity study in cotton ecosystem is very important to understand pest species affect on cotton production. In order to study biodiversity of insect pests on Bt and Non-Bt cotton ecosystems an attempt was made from July 2018 to January 2019 kharif cropping season in farmers Bt and Non-Bt cotton fields. The results indicated that insect pests were recorded from three insect orders viz Hemiptera, Lepidoptera and Orthoptera. A total 4768 individuals insects on Bt cotton, 5232 individuals insects on Non-Bt cotton fields were recorded with help of sweep net and hand picking. Insect pests were identified with the help of Guide on cotton pests, Regional Agricultural Research Station PJTSAU Warangal and literature. Twenty-two species on Bt cotton, Thirty-one species on non-Bt cotton were identified. The result indicates that significant differences found between the Bt and non-Bt cotton fields. We concluded that Bt cotton exerts marked negative effective on the abundance of insect pests. Various diversity indices were measured.